Revision of the subgenus Chalcotaenia of Paracupta (Coleoptera: Buprestidae: Chrysochroinae) and specification of Buprestis xanthocera Boisduval, 1835 as the type-species of the genus Paracupta - Frank, David (Zootaxa, 2024)
Subgenus Chalcotaenia Deyrolle, 1864 of Paracupta Deyrolle, 1864 is revised based on comparative study of extensive material including types of all described taxa. Buprestis xanthocera Boisduval, 1835 is specified as the type-species of genus Paracupta Deyrolle, 1864 and redescribed. Four new species are described: Paracupta (Chalcotaenia) gottwaldi sp. nov. from Solomon Islands: Ranongga Island; P. (C.) horaki sp. nov. from Indonesia: Seram Island; P. (C.) jakli sp. nov. from Solomon Islands: Guadalcanal and Malaita islands; P. (C.) laperousei sp. nov. from Indonesia: Bacan, Halmahera and Mandioli islands. Neotype is designated for Chrysodema lamberti Laporte de Castelnau & Gory, 1837 [Paracupta (Chalcotaenia) lamberti] and lectotype is designated for Buprestis xanthocera Boisduval, 1835 [Paracupta (Paracupta) xanthocera] to ensure their correct application and recognition in future. One new synonymy of subgenus: Paracupta Deyrolle, 1864 = Bojasinskia Hołyński, 2009 and one new synonymy of species: Buprestis xanthocera Boisduval, 1835 = Paracupta leveri Théry, 1934 are established. Paracupta isabellina Kerremans, 1900, P. rennelli Hołyński, 2014 and P. toxopeusi Obenberger, 1932 are transferred to subgenus Chalcotaenia. All herein included taxa are illustrated with colour photographs of habitus and the male aedeagus. A key to all taxa is presented.